2017
DOI: 10.1021/jacs.7b04884
|View full text |Cite
|
Sign up to set email alerts
|

Orchestrating Directional Molecular Motions: Kinetically Controlled Supramolecular Pathways of a Helical Host on Rodlike Guests

Abstract: An aromatic oligoamide sequence was designed to fold and self-assemble into a double helical host having a cylindrical cavity complementary to linear oligocarbamate guests. Formation of helical pseudorotaxane complexes, foldaxanes, between the host and guests having binding stations of different affinities was evidenced by NMR and X-ray crystallography. Rodlike guests possessing two or three binding stations, long alkyl or oligoethylene glycol spacers or bulky barriers in-between the binding stations, and a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…A related heteroundecamer host with two additional quinoline units, Piv-PDCA 3 -(7-amino-8-fluoro-2-quinolinecarboxylic acid) 8 -Boc, was also used with rationally designed rod-like guests with a very bulky stopper at only one extremity [ 159 ]. These experiments followed the first experiences with foldaxanes made of the same double-helical foldamer threading on mono-station (dicarbamates) or double-station (two dicarbamate anchoring stations) rod-like guests, for which no end-capping was used.…”
Section: Aromatic Foldamersmentioning
confidence: 99%
“…A related heteroundecamer host with two additional quinoline units, Piv-PDCA 3 -(7-amino-8-fluoro-2-quinolinecarboxylic acid) 8 -Boc, was also used with rationally designed rod-like guests with a very bulky stopper at only one extremity [ 159 ]. These experiments followed the first experiences with foldaxanes made of the same double-helical foldamer threading on mono-station (dicarbamates) or double-station (two dicarbamate anchoring stations) rod-like guests, for which no end-capping was used.…”
Section: Aromatic Foldamersmentioning
confidence: 99%
“…Helices based on 7‐amino‐8‐fluoro‐2‐quinolinecarboxylic acid oligoamides such as 1 possess a tubular cavity that can accommodate α,ω‐alkanediamine‐derived dicarbamate guests and slide along them. Threading and sliding of these helices along guests are much faster than their direct unwinding and rewinding, allowing for the design of kinetically favored supramolecular pathways depending on whether bulk too large to pass through the helix cavity is on the way or not . Solution and solid state data demonstrated that helix‐rod association is mainly driven by hydrogen bonds between carbamate carbonyl groups on the rods and 2,6‐pyridinedicarboxamide protons on the helix carbamate cleft (CC in Figure b).…”
Section: Figurementioning
confidence: 99%
“…This positive curvature and the saturation observed at two equivalents indicates that quenching is not purely due to collisional or dynamic quenching and reveals a static quenching process attributed to the formation of the donor-acceptor association 1•7. [14][15][16]…”
Section: This Journal Is © the Royal Society Of Chemistry 2017mentioning
confidence: 99%
“…These elegant structures have already allowed outstanding achievements in research fields as different as HIV treatment, 9 drug delivery, 10 catalysis 11,12 or molecular machinery. [13][14][15][16] All these discoveries lie on the rich supramolecular chemistry of foldamers and, more particularly, helical foldamers. The latter are very appealing chemical entities since the modification of their primary structure allows for i) tuning the number of loops 17 and their hybridization ability (foldamers can form double, triple or quadruple helices), [18][19][20] ii) inducing a desired handedness, 21,22 and iii) modulating the volume, the shape and the surface potential of the cavity formed upon folding.…”
mentioning
confidence: 99%